Efforts to Improve Long Jump Learning Achievement Through 50-Meter Sprint Training - Endrawan, I Bagus; Muslimin,; Atesya Kesumawati, Selvi; Sartika, Dewi (Indonesian Journal of Physical Education and Sport Science, 2023)
Study purpose. Many students are less active when participating in sports subjects, especially the Long Jump. As described above, it attracted the author's interest to try to conduct class action research with the title Efforts to Improve Long Jump Learning Achievement Through 50 Meter Fast Running Exercises. Materials and Methods. The method used was Classroom Action Research (PTK) often called action research, where this research was carried out through several cycles in the expectation of an increase in the results to be achieved, including (a) Lesson Planning, (b) Action Implementation, (c) Observation, and (d) Reflection Results. In cycle I, the average score was obtained with poor/low criteria, the average result of the learning completeness criteria was 48%. Furthermore, in cycle II, the average score was obtained with good criteria, the average result of the learning completeness criteria was 98%. Data was obtained from 25 students, the lowest score was 69 by Aprilia Pranadia and the highest score was 86 by Ibrahum Nasir. Conclusion. By using the 50-metre sprint learning method, students' ability to perform the long jump can improve. The ability of students to take part in learning by using the Sprint Run method from cycles I and II had increased, namely student completeness reached 99% based on the Minimum Completeness Criteria (KKM) value.